The Use of Canva Interactive Media to Motivate Students in ICT Learning in Elementary Schools in Bengkulu City - Nur Afifah Rohmah; Asmara Yumarni; Meirita Sari (CV. Edujavare Publishing, 2026)
The development of information and communication technology encourages teachers to utilize digital learning media that can create a more interactive, engaging, and student-centered learning process. One of the media widely used in learning is Canva because it provides various visual features that support creative delivery of materials. This study aims to describe the use of Canva interactive media in motivating students in Information and Communication Technology (ICT) learning in grade III at SD Islam Al-Azhar 51 Bengkulu City and describe the advantages of Canva interactive media in supporting the learning process. This study uses a qualitative approach with a descriptive research type. Data collection was carried out through observation, interviews, and documentation involving the principal, ICT subject teachers, and grade III students as research informants. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, while data validity was obtained through source triangulation and technical triangulation. The results of the study indicate that the use of Canva interactive media was carried out through the planning, implementation, and evaluation stages of learning. Teachers utilize Canva's various features, such as templates, images, animations, illustrations, icons, and interactive presentations, to present material in a more engaging manner, encouraging students to demonstrate attention, interest, engagement, and enthusiasm throughout the learning process. Furthermore, Canva offers advantages such as ease of use, attractive visuals, flexible access, and supports teachers in developing creative, innovative, and student-centered learning media. The use of Canva's interactive media provides a more engaging learning experience, making it an alternative digital learning medium for ICT instruction in elementary schools.